Attracting tourists to travel companies’ websites: the structural relationship between website brand, personal value, shopping experience, perceived risk and purchase intention - Mohseni, Shahriar; Jayashree, Sreenivasan; Rezaei, Sajad; Kasim, Azilah; Okumus, Fevzi (Routledge, 2018)
This article aims to examine the structural relationship between website brand, personal value, shopping experience, perceived risk and purchase intention from travel websites. Built upon the theory of consumers’ perceived risk, a theoretical model was proposed and a questionnaire was developed. The fieldwork utilized responses from 409 participants who purchased travel items from websites of Malaysian travel companies. Partial least square (PLS) path modelling approach, a variance-based structural equation modelling (VB-SEM), was used to assess the overall goodness-of-fit tests, measurement and structural model. The results highlight different aspects related to the effectiveness and attractiveness of travel companies’ websites. Its unique finding highlights the importance of personal value as a user characteristic factor that can strongly affect online purchase intention. In addition, by combining user characteristics and website characteristic and examining them in a single model, this study provides a clear multidimensional picture of causal relationship between latent constructs in an online travel purchase context. Theoretical and practical implications of study results are discussed and suggestions for future research are provided.